ANALISIS DRUG RELATED PROBLEMS (DRPs) PADA PASIEN RAWAT JALAN DIABETES MELITUS TIPE 2 DI UPT PUSKESMAS RAWAT INAP GEDONG AIR BANDAR LAMPUNG - Akhmad Rokiban; Dwiauliaramdini Dwiauliaramdini; Sitijuwariyah Sitijuwariyah (Fakultas MIPA Universitas Tulang Bawang Lampung, 2020)
Abtract Diabetes mellitus (DM) is a serious chronic disease that occurs because the pancreas does not produce enough insulin or when insulin is not use effectively in the body. This study aims to analyze the incidence of Drug Related Problems (DRPs) and find out the category of DRPs in outpatients with a diagnosis of type 2 diabetes mellitus at UPT Puskesmas Gedong Air Inpatient for the Bandar Lampung. This research is a nonexperimental research with a descriptive design taken retrospectively. The sampling technique used in this study is total sampling based on the patient's medical record data. Data were analyzed using the classification of DRPs according to Cipolle 2004, then using Medscape Tools as a tool to check potential drug interactions. The results of this study were 61 patients including 29 patients (46%) with DRPs and 33 patients (54%) without DRPs. The number of male patients is 25 patients and the number of female patients is 36 patients with age range 25-45 and 46-65. A total 52 patien Type 2 Diabetes Mellitus have cormobid and 9 patients without comorbid. DRP categories that occur include drugs without indication as much (8%), indications without drugs as much as (15%), and potential drug interactions (48%). The conclusion in this study is that Drug Related Problems (DRPs) have occurred in outpatients diagnosed with type 2 diabetes mellitus in UPT Puskesmas Gedong Air Inpatient with the highest DRPs category is the potential for drug interactions (48%). Key words: Diabetes Mellitus Type 2, Drug Related Problems